Determination of the characteristic frequency of two–level system in the modulated optical field - Jankauskas, Z.; Kvedaras, V.; Zaveckas, V. (Elektronika ir Elektrotechnika, 2006)
Interaction between a two-level system and strong nonmonochromatic electromagnetic field has been the focus of attention of the laser technique and fiber optics for a long time. The influence of the modulated optical signal on the active medium, when the amplitude and phase (or frequency) vary arbitrary in time, is important in many problems, such as interaction of ultrashort pulses with the resonant amplifier, change of the line shape, the emission perturbation theory, self-focusing of light, etc. In this article, a new computational procedure is proposed for a two-level system in the strong harmonically modulated optical field. Expressions for polarization and population difference of a quantum system have been obtained in the form of the Fourier series. The characteristic frequency has been determined numerically. It depends not only upon the intensity of the carrier wave and the detuning magnitude but also upon the depth and frequency of modulation. The computational technique is applicable both for amplitude and phase modulation. Ill. 6, bibl. 3 (in English; summaries in English, Russian and Lithuanian).